Single-Prolonged Stress Impairs Prefrontal Cortex Control of Amygdala and Striatum in Rats - Piggott, Veronica M.; Bosse, Kelly E.; Lisieski, Michael J.; Strader, John A.; Stanley, Jeffrey A.; Conti, Alana C.; Ghoddoussi, Farhad; Perrine, Shane A. (Frontiers in Behavioral Neuroscience, 2019)
Medial prefrontal cortex, amygdala, and striatum neurocircuitry has been shown to play an important role in post-traumatic stress disorder (PTSD) pathology in humans. Clinical studies show hypoactivity in the medial prefrontal cortex and hyperactivity in the amygdala and striatum of PTSD patients, which has been associated with decreased medial prefrontal cortex glutamate levels. The ability to refine neurobiological characteristics of PTSD in an animal model is critical in furthering our mechanistic understanding of the disease. To this end, we exposed male rats to single prolonged stress (SPS), a validated model of PTSD, and hypothesized that traumatic stress would differentially activate medial prefrontal cortex subregions (prelimbic and infralimbic cortices) and increase striatal and amygdalar activity, which would be associated with decreased medial prefrontal cortex glutamate levels. In vivo, neural activity in the subregions of the medial prefrontal cortex, amygdala, and striatum was measured using manganese-enhanced magnetic resonance imaging (MEMRI), and glutamate and N-acetylaspartate levels in the medial prefrontal cortex and the dorsal striatum were measured using proton magnetic resonance spectroscopy (1H-MRS) longitudinally, in rats exposed to SPS or control conditions. As hypothesized, SPS decreased MEMRI-based neural activity in the infralimbic, but not prelimbic, cortex concomitantly increasing activity within the basolateral amygdala and dorsomedial striatum. 1H-MRS studies in a separate cohort revealed SPS decreased glutamate levels in the medial prefrontal cortex and increased N-acetylaspartate levels in the dorsal striatum. These results confirm previous findings that suggest SPS causes medial prefrontal cortex hypoactivation as well as identifies concurrent hyperactivation in dorsomedial striatum and basolateral amygdala, effects which parallel the clinical neuropathology of PTSD.